Robo therapist: a sustainable approach to teach basic expressions for special needs children in Malaysia - Zharif Amin, Muhammad; Zamin, Norshuhani; Ab Rahim, Hazrita; Irdawaty Hassan, Nurmala; Diyana Kamarudin, Nur (International Journal of Engineering and Technology, 2018)
Social interaction is an essential component for development of both normal and special needs children. However, many special needs children suffer from a lack of social interaction because they are unable to interpret social cues as well as a failure in social gaze when communicating. One of the ways to cope with these problems is to improve their social cognitive skill by teaching basic emotions through facial expressions. This paper describes the development of a new and sustainable teaching and learning approach using robotics to promote social interaction among special needs children of aged 4-6 years old. The robotic tool can teach basic facial expressions such as happy, sad and angry to increase emotion recognition skill among special needs children. The growing demand for technological innovation to enable empowerment of developing communities requires new and creative educational initiatives. Malaysia has also address it concerns on sustainable education for all spectrum of communities. RoboTherapist is a new teaching and learning method in Malaysiaâ€™s special education which targeting the special needs children. The special needs children are children with Autism, children with Down Syndrome, children with ADHD and slow learners. The aim of this research is to make teaching and learning more attentive for special needs children and hence to improve their social interaction in daily is life and gain confidence to communicate with the people around them.Â